A bibliometric and systematic literature review of seagrass conservation for sustainable management. - Wardi Kurniawan; Dana Ainal Hasan (Journal of Biology, Environment, and Edu-Tourism, 2025)
This study explores sustainable seagrass management in Gili Kondo, Indonesia, through a Systematic Literature Review (SLR), bibliometric mapping, and Likert-scale surveys of local fishermen. The aim is to assess global and national trends in blue carbon, ecosystem services, and community-based conservation, while analyzing fishermen’s perceptions of conservation and policy. Bibliometric results identify four research clusters: ecological resilience, blue carbon, community engagement, and policy integration. Quantitative analysis shows high knowledge (mean = 4.3) and positive conservation attitudes (mean = 4.1), but moderate perceptions of government support (mean = 3.2). Findings indicate that community awareness is strong, yet policy and institutional coordination require improvement. The study concludes that adaptive, science-based, and participatory governance is crucial for sustaining seagrass ecosystems. This research contributes to strengthening blue carbon policy frameworks and provides a replicable model for coastal management in small island regions.